Preparation of composite wire FexNi100-x/Cu with Magnetoimpedance (MI) effect. Part II. Relation between composition, structure, magnetic properties and MI effect - Tung et al, Mai Thanh (Vietnam Journal of Chemistry, 2014)
Relation between composition and structure, magnetic properties and magnetoimpedance (MI) effect of electrodeposited composite wire FexNi1-x/Cu were investigated. Results showed that the increase of Fe content enhanced the bcc phase and decreased the grain size of the deposited alloy. The coercively Hc of the composite wire FexNi100-x/Cu varied with composition and achieved the lowest value of 1.49 Oe with the wire composition of Fe54Ni46/Cu. MI effect was strongly influenced by the wire composition and corresponded well with the change of coercively. the maximum values of MIrmax were 110% (f = 4.5 Hz) and 23% (f = 10.7 Hz) with the wire composition of Fe54Ni46/Cu.